Development of a Microbial Fuel Cell Cocatalyst with Propionibacterium freudenreichii ssp. shermanii - Johnson, Jessica Virginia (Université d'Ottawa / University of Ottawa, 2018)
Addressing the low power generation of anodic biocatalysts is pertinent to the advancement of microbial fuel cell technology. While Propionibacterium freudenreichii ssp. shermanii has shown potential as a biocatalyst, its incomplete consumption of the anodic substrate is a persistent issue. This research aims to optimize substrate consumption to increase power generation using Propionibacterium freudenreichii ssp. shermanii as a biocatalyst. The effect of coculturing Geobacter sulfurreducens with Propionibacterium freudenreichii ssp. shermanii was investigated. The cocatalyst and pure culture performance was tested in an air-cathode microbial fuel cell. Geobacter sulfurreducens produced the highest maximum power density among the experimental cases. Power density produced by Propionibacterium freudenreichii ssp. shermanii was improved in the air-cathode design compared to previous experiments performed in an H-type design. The novel cocatalyst was shown to produce electricity, however a full characterization to elucidate the contribution to power generation by each microbe would be desirable to investigate.
Keywords: microbial fuel cell; biocatalyst; Propionibacteria; Geobacter; cocatalyst; renewable energy; clean technology; air-cathode